Toll-Like Receptor Signaling Pathways—Therapeutic Opportunities. (17th October 2010) - Zhu, Jiankun; Mohan, Chandra
Abstract : Toll-like receptors (TLRs) are transmembrane proteins acting mainly as sensors of microbial components. Triggering TLRs results in increased expression of multiple inflammatory genes, which then play a protective role against infection. However, aberrant activation of TLR signaling has a significant impact on the onset of cancer, allergy, sepsis and autoimmunity. Various adaptor proteins, including MyD88, IRAKs, TIRAP, TRIF, and TRAM, are involved in specific TLR signaling pathways. This article reviews the role of these molecules in TLR signaling, and discusses the impact of this pathway on various disease scenarios. Given their important role in infectious and non-infectious disease settings, TLRs and their signaling pathways emerge as attractive targets for therapeutics.